Reading Catullus 113 as the Vilification of Pompey's Ex-Wife Mucia. (2021) - Hillard, Tom
Abstract: Written in 55 BCE, carmen 113 seemingly uses the first two consulships of Pompey to measure a decline in moral standards, with one unfortunate woman as the yardstick of sexual profligacy. It closes with a focus on marital infidelity. The epigram should be read as a savage attack upon Mucia, the one-time wife of Pompey. This paper affirms her identity by postulating a punning wordplay on Mucia and C(a)ecilia that made this identification clear to the poet's readership. No textual emendation is required. It is also proposed that the observation regarding adultery, no mere aphorism, queried the legitimacy of one or more of Pompey's children.